Radiographic Evaluation of Keel Bone Damage in Laying Hens—Morphologic and Temporal Observations in a Longitudinal Study - Baur, Sarah; Rufener, Christina; Toscano, Michael J.; Geissbühler, Urs (Frontiers in Veterinary Science, 2020)
The keel bone of commercially kept laying hens is known to be frequently affected by morphologic changes such as fractures and deformations with important implications for animal welfare. To detect morphologic changes, various methods such as palpation, computed tomography and ultrasound are available, though radiography allows for the greatest level of detail in combination with the most ease of use. To explore the benefits of radiography in providing objective data on keel fractures from the age of 22 to 61 weeks within a single laying period, the keel bones of 75 Lohmann Brown and 75 Lohmann Selected Leghorns were radiographed every three to five weeks. Type, location, angulation, dislocation, callus formation, and healing process were assessed descriptively for each lesion. Ninety-nine percent of the animals showed at least one keel bone lesion during the study and 97% of the animals had at least one keel bone fracture. In 77% of the cases, the caudal third of the keel bone was affected. The fracture types were transverse and oblique (88%), comminuted, and butterfly. Further lesions were sclerosis, new bone formation and angulation. For each keel bone, an average of three fractures (3.09 +/- 1.80) was detected at the end of the study. The described radiographic protocol for keel bone lesions was suitable for longitudinal, on-site examinations in conscious laying hens. Our results also indicate that keel bone fractures are more frequent than reported in earlier studies. The described radiographic examination protocol can be used to perform comparative studies of palpatory findings, or to assess the clinical significance of different fracture types which require a high level of detail.